Effect of Adding Granul Basil (Ocimum americanum) as Antioxidants in Fried Foods - Deden I Dinata; Dadih Supriadi; Garnadi Djafar; Syerliana Syerliana; Wahyu Wijayanti; Shelvy E Suherman (Indonesian Journal of Pharmaceutical Science and Technology, 2015)
Basil is one of medicinal plants in Indonesia that has been used empirically as antimicrobes, analgetic, antiinflammatory, antivirus, antitumor, and antioxidants that prevented ischemia. This research aimed to investigate the effect of adding granule ethanol extract of basil leaves (Ocimum americanum) as antioxidant to capture free radicals in fried foods. The antioxidant activity of ethanol extract of basil leaves with DPPH determinated by IC50, comparing the antioxidant activity of the granule and the control by determination of quality properties of oil and food after frying using Fourier Transfor Infra Red (FTIR) spectra, and quantitative parameters by determination percentage of free fatty acid (FFA). Results of maceration with ethanol 15.94% w/w, total ash content 9.85%, water soluble ash content 3.98%, acid insoluble ash content 3.98%, water soluble extract 25.89%, ethanol soluble extract 12.76%, water content 6.87%, drying shrinkage 11.19%. Testing the antioxidant activity of the ethanol extract of basil leaves with DPPH gave IC50 of 80.55 ppm. The result of antioxidant testing by determination percentage of FFA statistically with ANOVA (significance 0.00<5) and comparison of the concentration extract in basil granule with LSD test significantly different. The result indicates that adding ethanol extract of granules basil on fried foods gave antioxidant activity because it can inhibit the increasing of FFA percentage. Keywords: Antioxidant, basil leaves, DPPH, granule